2005
DOI: 10.1029/2004jc002615
|View full text |Cite
|
Sign up to set email alerts
|

Silica fluxes in the northeast Atlantic frontal zone of Mode Water formation (38°–45°N, 16°–22°W) in 2001–2002

Abstract: [1] The biogenic (BSi) and lithogenic (LSi) silica export fluxes were investigated in the northeast Atlantic (38°- at 1000 m) was lower than BSi and accounted for 10% of the total silica export flux.45°NResults show a strong coupling between the two siliceous particulate fractions, which is interpreted as reflecting LSi scavenging by BSi and limitation of BSi production in surface water by lithogenic (trace metals) inputs. BSi export was maximum at the beginning of the productive season during the spring bloom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…8 mg/m 2 /day; Uematsu et al, 2003). During almost all periods, lithogenic particle fluxes in the lower depth were greater than those in the upper depth, as reported previously (e.g., Honjo et al, 1982;Saito et al, 1992;Mosseri et al, 2005).…”
Section: Temporal and Vertical Lithogenic Particle Fluxessupporting
confidence: 66%
See 1 more Smart Citation
“…8 mg/m 2 /day; Uematsu et al, 2003). During almost all periods, lithogenic particle fluxes in the lower depth were greater than those in the upper depth, as reported previously (e.g., Honjo et al, 1982;Saito et al, 1992;Mosseri et al, 2005).…”
Section: Temporal and Vertical Lithogenic Particle Fluxessupporting
confidence: 66%
“…Lithogenic particles are transported to the ocean surface by atmospheric deposition and/or water movement (e.g., Otosaka et al, 2004;Mosseri et al, 2005). Lithogenic particles supply micronutrients and enhance biological activity in the surface ocean (Jickells, 1995(Jickells, , 1999Bonnet and Guieu, 2004) and act as ballast supporting the vertical transport of biogenic particles (Armstrong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the sinking lithogenic material compared to these end‐members for Al and Fe concentrations are reported in Figure 12. The Fe/Al ratio is close to the sediment shelf one for the samples collected at the NW site, both at 400 and 1000 m. It has to be noted that cup 1 at 400 m and 1000 m have a typical Saharan end‐member ratio that may be attributed to Saharan particles carried during a strong Saharan event that took place in the area at mid‐February [ Mosseri et al , 2005]. At the NE and SW sites, the Fe/Al ratio is intermediate between the shelf sediment and the Saharan end‐members indicating a probable mixed origin of the particles.…”
Section: Discussionmentioning
confidence: 58%
“…The organic matter fraction was calculated as 2 × (% POC). Biogenic (BSi) and lithogenic (LSi) silica were measured in Laboratoire d'Océanographie et de Biogéochimie (Marseille) and data can be found in Mosseri et al [2005]. By using the BSi data, the opal (SiO 2 , nH 2 O) fraction was determined (assuming that n = 0.4 [ Mortlock and Froelich , 1989]).…”
Section: Methodsmentioning
confidence: 99%
“…The particulate silica export fluxes ( B Si exp flux) were compared to other studies also conducted in the North Atlantic at similar latitudes (Table 4). Very similar B Si exp fluxes were obtained between the flux measured in drifting sediment traps deployed at each site at 400 m during the second legs and the average fluxes measured in moored sediment traps deployed over one year in the POMME study area [ Mosseri et al , 2005]. In most cases, B Si fluxes were measured at different depths (150–3000 m), but it has been shown that the B Si fluxes was conservative between the surface and deep traps in diverse oceanic systems, confirming the paradigm that diatoms are associated with rapid sedimentation events to depth [ Ragueneau et al , 2000].…”
Section: Discussionmentioning
confidence: 69%